2017
DOI: 10.1111/bjh.14650
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and treatment for iron deficiency in heart failure: the unmet need in Lower and Middle Income Countries

Abstract: Summary Frank iron deficiency has been associated with a wide range of cardiac and pulmonary abnormalities including non‐ischaemic cardiomyopathy. Iron deficiency anaemia and isolated iron deficiency are well‐defined adverse prognostic factors in non‐ischaemic cardiac failure. Furthermore, iron‐deficient patients in chronic heart failure with a serum ferritin of <100 μg/l or <300 μg/l with reduced transferrin saturation of <20%, who were given intravenous iron showed improved clinical outcomes. Iron deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…21 In nonischaemic cardiac failure, IDA is a well-defined adverse prognostic factor. 4,12,22,23 These study findings indicate that IDA plays a significant role in the function of the heart. In addition, the myocardium is a key factor in the pathophysiology of heart failure.…”
Section: Signs and Symptomssupporting
confidence: 52%
See 1 more Smart Citation
“…21 In nonischaemic cardiac failure, IDA is a well-defined adverse prognostic factor. 4,12,22,23 These study findings indicate that IDA plays a significant role in the function of the heart. In addition, the myocardium is a key factor in the pathophysiology of heart failure.…”
Section: Signs and Symptomssupporting
confidence: 52%
“…24,25 Anaemia and ID are common causes of heart failure, both separately and in combination. 22 Honda et al 14 showed that anaemia was an independent predictor of myocardial damage or subclinical myocardial damage and cardiovascular mortality in the general population. Current evidence suggests that ID and anaemia are more prevalent in patients with heart failure and reduced ejection fraction, as well as in those with heart failure and preserved ejection fraction.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Anemia is often reported in patients with heart failure (15.2%) in sub-Saharan Africa [7]. Anemia is associated with iron deficiency, requiring long-term treatment and multidisciplinary team supervision [14]. In Africa, in terms of living conditions and the lack of care, the prognosis in this context is poor [14].…”
Section: Discussionmentioning
confidence: 99%
“…-Anemia: hemoglobin < 12 g/dL in men, and <13 g/dL in women, or less than 2 units of usual value [14].…”
Section: Methodsmentioning
confidence: 99%
“…2 Serum iron levels are one of the most commonly measured markers in critically ill patients. Serum iron levels are closely associated with anemia, 6 severity of infection, 7 and cardiac failure, 8 all of which are common complications in critically ill patients and may affect the prognosis of patients. This retrospective, single-center study aimed to determine the relationship between serum iron levels and in-hospital mortality of critically ill patients in the ICU.…”
Section: Introductionmentioning
confidence: 99%